Cloning, mapping, and characterization of the Escherichia coli prc gene, which is involved in C-terminal processing of penicillin-binding protein 3. - Hara, H (1991)
The prc gene, which is involved in cleavage of the C-terminal peptide from the precursor form of penicillin-binding protein 3 (PBP 3) of Escherichia coli, was cloned and mapped at 40.4 min on the chromosome. The gene product was identified as a protein of about 80 kDa in maxicell and in vitro systems. Fractionation of the maxicells producing the product suggested that the product was associated with the periplasmic side of the cytoplasmic membrane. This was consistent with the notion that the C-terminal processing of PBP 3 probably occurs outside the cytoplasmic membrane: the processing was found to be dependent on the secY and secA functions, indicating that the prc product or PBP 3 or both share the translocation machinery with other extracytoplasmic proteins. DNA sequencing analysis of the prc gene region identified an open reading frame, with two possible translational starts 6 bp apart from each other, that could code for a product with a calculated molecular weight of 76,667 or 76,432. The prc mutant was sensitive to thermal and osmotic stresses. Southern analysis of the chromosomal DNA of the mutant unexpectedly revealed that the mutation was a deletion of the entire prc gene and thus that the prc gene is conditionally dispensable. The mutation resulted in greatly reduced heat shock response at low osmolarity and in leakage of periplasmic proteins.